Land management change greatly impacts biofuels' greenhouse gas emissions. Issue 6 (15th February 2018) - Qin, Zhangcai; Canter, Christina E.; Dunn, Jennifer B.; Mueller, Steffen; Kwon, Hoyoung; Han, Jeongwoo; Wander, Michelle M.; Wang, Michael
Abstract: Harvesting corn stover for biofuel production may decrease soil organic carbon (SOC) and increase greenhouse gas (GHG) emissions. Adding additional organic matter into soil or reducing tillage intensity, however, could potentially offset this SOC loss. Here, using SOC and life cycle analysis (LCA) models, we evaluated the impacts of land management change (LMC), that is, stover removal, organic matter addition, and tillage on spatially explicit SOC level and biofuels' overall life cycle GHG emissions in US corn–soybean production systems. Results indicate that under conventional tillage (CT), 30% stover removal (dry weight) may reduce baseline SOC by 0.04 t C ha −1  yr −1 over a 30‐year simulation period. Growing a cover crop during the fallow season or applying manure, on the other hand, could add to SOC and further reduce biofuels' life cycle GHG emissions. With 30% stover removal in a CT system, cover crop and manure application can increase SOC at the national level by about 0.06 and 0.02 t C ha −1  yr −1, respectively, compared to baseline cases without such measures. With contributions from this SOC increase, the life cycle GHG emissions for stover ethanol are more than 80% lower than those of gasoline, exceeding the US Renewable Fuel Standard mandate of 60% emissions reduction in cellulosic biofuels. Reducing tillage intensity while removing stover could also limit SOC loss or lead to SOC gain, which would lower stover ethanol life cycle GHG emissions to near or under the mandated 60% reduction. Without these organic matter inputs or reduced tillage intensity, however, the emissions will not meet this mandate. More efforts are still required to further identify key practical LMCs, improve SOC modeling, and accounting for LMCs in biofuel LCAs that incorporate stover removal. Abstract : The study examined the impacts of land management change, that is, stover removal, organic matter addition, and tillage on spatially explicit soil organic carbon level and biofuels' overall life‐cycle GHG emissions in the U.S. Results show that, corn stover removal can result in soil carbon loss. Soil amendments (e.g., cover crop, manure) and reduced tillage intensity, however, could limit such loss or lead to soil carbon gain. With proper land management, the life‐cycle GHG emissions for stover ethanol could be lowered to near or under the U.S. mandate of 60% emissions reduction (relative to gasoline) for cellulosic biofuels.